LAYANAN INFORMASI OLEH GURU PEMBIMBING TENTANG PENGENDALIAN STRES DALAM BELAJAR DI SMPN 2 PONTIANAK - Simare Mare, Gresmid; Astuti, Indri; Yusuf, Abas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: This study aims to obtain an objective picture of Information Services by Supervising Teachers About Controlling Stress in Learning in Class VIII SMPN 2 Pontianak . The general problem in this study is